Siro - Ignatius, David 1950- (Farrar Straus Giroux, 1991)
Novel about a rogue CIA operation to "find a way to exploit the Soviet Union at its ragged edges--Uzbekistan, Azerbaijan, Armenia, Georgia."
Keywords: United States. -- Central Intelligence Agency -- Fiction; Politik; Cold War -- Fiction; Sowjetunion; Soviet Union -- Politics and government -- Fiction; Fiktionale Darstellung; Spy stories